2021
DOI: 10.1007/s12015-021-10217-8
|View full text |Cite
|
Sign up to set email alerts
|

The Treasury of Wharton's Jelly

Abstract: Background Postnatal umbilical cord tissue contains valuable mesenchymal progenitor cells of various differentiation stages. While mesenchymal stem cells are plastic-adherent and tend to differentiate into myofibroblastic phenotypes, some round cells detach, float above the adherent cells, and build up cell aggregates, or form spheroids spontaneously. Very small luminescent cells are always involved as single cells or within collective forms and resemble the common well-known very small embryonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…These data indicated that they could be indeed developmentally related to a population of migrating epiblast-derived PGCs [ 43 ]. In addition, like other research groups before us, we were able to show that VSEL-like cells have the ability to differentiate into stem cells of three different germ layers [ 16 , 44 ]. In this context it could be demonstrated that murine or human VSEL like cells were differentiable into neuron marker expressing cells in vitro [ 45 ] and in vivo [ 46 ].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…These data indicated that they could be indeed developmentally related to a population of migrating epiblast-derived PGCs [ 43 ]. In addition, like other research groups before us, we were able to show that VSEL-like cells have the ability to differentiate into stem cells of three different germ layers [ 16 , 44 ]. In this context it could be demonstrated that murine or human VSEL like cells were differentiable into neuron marker expressing cells in vitro [ 45 ] and in vivo [ 46 ].…”
Section: Discussionsupporting
confidence: 79%
“…The most common view is that cells of mesodermal tissues such as the UC can acquire properties of ectodermal cells by transdifferentiation and thereby become differentiable into neuronal cells [ 36 ]. Here we focus rather on the pluripotent stem cell fraction of the UC which were already discovered in our last study [ 16 ]. This pluripotent stem cell fraction consists of tiny roundish stem cells that were seen as single cells directly attached to large adherent stromal cells that were attached to the plastic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive analysis of embryonic stem cell line and bone marrow-derived MSCs did demonstrate great similarities in their cellular genetic and proteomic profiles [28]. Our study was inspired in part by a recently conducted analysis of cultured in vitro cell based system while the aim of our study was to characterize biological discard derived primary progenitor stromal cells, sorted cells and CNC, to leverage their signature features in developing application ready in vitro human surrogate microphysiological systems [29].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, we configured it by enriching the cellular population with the SSEA4 cells (30-72%) and further culture expanding them. Cells bearing this marker are known to have the capacity for triploblastic differentiation into three germ layers and selfrenewal [29]. The identification of SSEA4 positive cells from human tissue has precedence; SSEA4-positive cells have been previously identified from several human tissues like human fetal forebrain, forebrain-derived neurosphere cells, and human adult ovaries [31].…”
Section: Discussionmentioning
confidence: 99%